The Euro Area Crisis : Need for a Supranational Fiscal Risk Sharing Mechanism? - Furceri, Davide; Zdzienicka, Aleksandra (Washington, D.C. : International Monetary Fund, 2013)
The aim of this paper is to assess the effectiveness of risk sharing mechanisms in the euro area and whether a supranational fiscal risk sharing mechanism could insure countries against very severe downturns. Using an unbalanced panel of 15 euro area countries over the period 1979-2010, the results of the paper show that: (i) the effectiveness of risk sharing mechanisms in the euro area is significantly lower than in existing federations (such as the U.S. and Germany) and (ii) it falls sharply in severe downturns just when it is needed most; (iii) a supranational fiscal stabilization mechanism, financed by a relatively small contribution, would be able to fully insure euro area countries against very severe, persistent and unanticipated downturns.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet